Brief ethanol doses modifies 5HT levels at Raphe obscurus in neonate rats - Macchione, Ana Fabiola (2017)
Fil: Macchione, Ana Fabiola. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigación Médica Mercedes y Martín Ferreyra; Argentina.